The Influence of Green Accounting and Corporate Social Responsibility on Firm Value with Profitability as a Moderating Variable - Aryani, Dwi Nita; Damayanti, Made Dwi (Maneggio, 2025)
This research aims to analyze Green Accounting and Corporate Social Responsibility on Firm Value with Profitability as a moderating variable. In this research, Green Accounting and CSR are used as independent variables, Profitability as a moderating variable, and the dependent variable used is firm value. The research sample is seven companies that joined IDX Carbon for the 2018-2022 period which were selected using a purposive sampling technique hence total data collected is 35. The analysis method uses multiple linear regression and moderated regression analysis with SPSS 25 as statistical tools in this research. The results show that Green Accounting has a positive and significant effect on firm value, Corporate Social Responsibility has a significant effect on firm value, Profitability is not able to moderate the relationship between Green Accounting and firm value, Profitability is not able to moderate the relationship between Corporate Social Responsibility and firm value. It is hoped that the results of this research can be a consideration for investors, companies and theories development).